COMPARATIVE ANALYSIS OF THE ECOLOGICAL AND ECONOMIC CONDITION OF THE TERRITORIES OF THE VELAYATS OF THE REPUBLIC OFTURKMENISTAN - E. Bondar; V. Movsesova (Наука. Инновации. Технологии, 2022)
Introduction. In 2017 The Republic of Turkmenistan has adopted Law No. 569-v on environmental safety, which is an indicator of the severity of environmental and resource problems. This article attempts to provide an integrated assessment of the current state of the natural resource potential of the country based on the methodology for assessing the ecological and economic balance of the territory. This will allow us to solve the problems of effective use of land resources and improvement of disturbed areas. Materials and methods of research. The methodology proposed by B. I. Kochurov is the most appropriate for understanding the ecological state of administrative units. The degree and vector of anthropogenic impact, the level of ecosystem stability in this method are evaluated in the characteristics of the ecological and economic balance of the territory. The analysis of the structure of land use was carried out on the basis of the classification units used in the statistical yearbooks of Turkmenistan of the National Institute of State Statistics and Information Turkmenmillihasabat. Research results and their discussion. Calculations of the coefficients of absolute and relative tension and natural protection for 5 velayats of the republic are presented. It is established that the coefficient of natural protection of the territory of the Balkan velayat differs greatly from other administrative units. Conclusions. The results of the spatial distribution of the coefficients characterizing the ecological and economic balance in the velayats of the republic show some discrepancy in the indicators. The considered indicators of the ECB of the region are related to the structure of land use, the degree of intensity of agriculture, the presence of natural ecosystems and the development of the network of specially protected areas.